Abundance and distribution of Ulva microscopic propagules associated with a green tide in the southern coast of the Yellow Sea - Yuanzi, Huo; Liang, Hua; Hailong, Wu; Jianheng, Zhang; Jianjun, Cui; Xiwen, Huang; Kefeng, Yu; Honghua, Shi; Peimin, He; Dewen, Ding (Harmful algae, 2014)
•Large biomass of Ulva propagules existed widely during the blooming process.•The quantity of Ulva propagules decreased sharply after the bloom disappearing.•Ulva propagules were significantly correlated with salinity, turbidity and nutrients. The presence of Ulva microscopic propagules may play an important role in the rapid development of high-biomass blooms of green algae in the Yellow Sea. Six cruises were conducted, to determine the abundance and distribution of Ulva microscopic propagules associated with a green tide that developed in the southern coastal waters of the Yellow Sea from April to August, 2012. Results indicated that Ulva microscopic propagules were widespread in these waters, with the highest density being up to 4800ind.L−1, prior to the appearance of the green tide in April. High densities were also widely distributed along the coast during May and June, after the appearance of the floating green tide. The quantity of Ulva microscopic propagules significantly decreased when the floating green tide declined in July, reaching densities of up to 162ind.L−1, following the disappearance of the floating green tide in August. Quantitative studies on the distribution patterns of Ulva microscopic propagules along the southern coast of the Yellow Sea indicated a significant correlation between density and salinity, turbidity and nutrient concentrations. Temporal and geographical distribution patterns of Ulva microscopic propagules were also significantly affected by the presence of a large biomass of attached, or floating, Ulva species algae.